PREVENTION AND MANAGEMENT OF DENTURE STOMATITIS: Pencegahan dan Tatalaksana Denture Stomatitis - Indriani Oktaria (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Introduction: Denture Stomatits (DS) is pathological changes in the oral mucosa that commonly occurs in denture users, which is characterized by an inflammatory reaction amd erythema in the area of the oral mucosa that is in contact with the denture. Review: There are 3 types of Denture Stomatitis, in order: tipe I Hyperemic Pinpoint lessions (Localized Simple Inflammation), type 2 Generalized Simple Inflammation , type 3 Inflammatory Papillary Hyperplasia . In general, DS occurs on the palatal mucosa. Risk factors such as trauma from occlusion from excessive dentures, poor OH and degenerative conditions ( systemic) are not good and had habbits such as smoking increase the occurrence of DS. The appearance of reddish lessions that occur in the palatal mucosa without symptoms of severe pain is one of the clinical features of DS condition. The diagnosis of DS can be made by clinical examination and microscopic tissue culture examination. Conclusion: Repairing dentures and making changes to the condition of oral hygene is one of the keys to success in accelerating the healing of DS. In addition, if there is a fairly severe candidiasis, topical and systematic antifungal drugs can be given to recover the condition.